Extratropical Atmospheric Predictability From the Quasi‐Biennial Oscillation in Subseasonal Forecast Models. Issue 15 (3rd August 2018) - Garfinkel, Chaim I.; Schwartz, Chen; Domeisen, Daniela I. V.; Son, Seok‐Woo; Butler, Amy H.; White, Ian P.
Abstract: The effect of the Quasi‐Biennial Oscillation (QBO) on the Northern Hemisphere wintertime stratospheric polar vortex is evaluated in five operational subseasonal forecasting models. Of these five models, the three with the best stratospheric resolution all indicate a weakened vortex during the easterly phase of the QBO relative to its westerly phase, consistent with the Holton‐Tan effect. The magnitude of this effect is well captured for initializations in late October and November in the model with the largest ensemble size. While the QBO appears to modulate the extratropical tropospheric circulation in some of the models as well, the importance of a polar stratospheric pathway, through the Holton‐Tan effect, for the tropospheric anomalies is unclear. Overall, knowledge of the QBO can contribute to enhanced predictability, at least in a probabilistic sense, of the Northern Hemisphere winter climate on subseasonal timescales. Plain Language Summary: The Quasi‐Biennial Oscillation (QBO) is perhaps the most regular atmospheric phenomena that is not directly controlled by solar radiation and can be predicted more than a year in advance. It is characterized by alternating westerly and easterly winds in the tropical stratosphere. Here we show that the QBO can be used to improve month‐ahead prediction of the Northern Hemisphere wintertime stratospheric polar vortex, and perhaps even the extratropical tropospheric circulation. Key Points: QBO can contribute to enhanced predictability, in a probabilistic sense, of the Northern Hemisphere climate on subseasonal timescales Operational subseasonal forecasting models with reasonable stratospheric resolution capture the Holton‐Tan effect Anomalies may propagate down to surface, though some ambiguities exist